EFEKTIVITAS EDUKASI BAHAYA PERNIKAHAN DINI TEHADAP PENGETAHUAN REMAJA PUTRI - Yulianti Yulianti (NHM PRESS, 2023)
Marriage is a union of bonds between a man and a woman in such a way that they become husband and wife who are legally married according to religion and country. the purpose of this study was to determine the effectiveness of education on the dangers of early marriage on young women's knowledge. The sample used in this study was 30 young women in Karangraharja Village. sampling technique using the Random Sampling Sample Technique. The statistical analysis used in this study was the Paired Sample T test. The research results obtained in the study with a P-value of 0.000 <0.05, which means that the educational method used is effective in increasing the knowledge of young women about early marriage.